Answer: infinitely many solutions.
Step-by-step explanation:
Ok, our equation is:
-2.1*b + 5.3 = b - 3.1*b + 5.3
now, simplifyng the right side, we have:
b - 3.1*b + 5.3 = (1 - 3.1)*b + 5.3 = -2.1*b + 5.3
Then our initial expression is:
-2.1*b + 5.3 = -2.1*b + 5.3
So in both sides of the equality we have the exact same thing, so this is a trivial equality.
This means that the equality will remain true for any value of b, which means that we have infinitely many solutions.
Answer:
There are 336 teenagers in the concert. Please Mark me brainliest if I am correct thank you and have a nice day.
Step-by-step explanation:
Answer:
(x + 4) and (x + 1)
Step-by-step explanation:
x² + 5x + 4
Consider the factors of the constant term (+ 4) which sum to give the coefficient of the x- term (+ 5)
The factors are 4 and 1 , since
4 × 1 = 4 and 4 + 1 = 5 , then
x² + 5x + 4 = (x + 4)(x + 1) ← in factored form
9514 1404 393
Answer:
(a) f(x) = √x -2
Step-by-step explanation:
The square root function has no horizontal shift, so the expression under the radical is simply x with no added terms. There is only one such answer choice, which also shows the necessary translation downward by an added negative constant.
![f(x)=\sqrt{x}-2](https://tex.z-dn.net/?f=f%28x%29%3D%5Csqrt%7Bx%7D-2)
You can round each number to the nearest half
12 3/8 = 12 1/2
6 7/8 = 7
Now, you have: 12 ½ × 7
Since you have a mixed number, change it to a decimal to make it easier.
12 ½ = 12.5
12.5 × 7 = 87.5
The product of 12 3/8 and 6 7/8 is about 87 1/2 = 87.5
~Aamira~
Hope this helped :)